Decision-Making Model for the Selection of Industrial Sector Workers - Anggara, Ikbal; Kusumah, Lien Herliani (Universitas Al Azhar Indonesia, 2024)
Recruitment of workers must be done selectively to match the industry's needs for skills and competencies. How ever in Karawang area with the existing capacity performance capacity of the workforce; only 2.5 percent of total job seekers were successfully placed. This study aims to determine the selection criteria for industrial sector workers and provide recommendations for decision-making models for the selection process. To determine the priority criteria, the AHP method was used, followed by the TOPSIS method to calculate preferences. 3 respondents from the Employers' Association of Indonesia (APINDO), HRD-GA Association, and Dinas Tenaga Kerja & Transmigrasi Karawang were requested to act as the experts on employment matters for this study. It was found from this study that Educational, discipline, and skills are three of the fifteen priority criteria with the highest scores in succession. Individual Factors are also being recommended as a priority factor in selecting workers for the industrial sector.Keywords – AHP, TOPSIS, MCDM, Industrial Sector, Workforce Selection.